Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T23:04:05+01:00
A(2a+1) dla a=1,a=-2,a=-1,a=4

poprostu podstawiasz pod a.

dla a=1
2a+1=2*1+1=2+1=3

dla a=-2
2*-2+1=-4+1=-3

dla a =-1
2*-1+1=-1+1=0

dla a=4
2*4+1=8+1=9
2010-03-02T23:06:22+01:00
A(2a+1) dla a=1 a=-2 a=-1 a=4
1(2*1+1)=2+1=3
-2(2*(-2)+1=-4*(-2)+1=8+1=9
-1(2*(-1)+1=-2*(-1)+1=2+1=3
4(2*4+1)=4(9)=36
2010-03-02T23:23:42+01:00
Zad.
a(2a+1) dla a=1,a=-2,a=-1,a=4

podstawiasz za a kolejno 1, -2, 4.
odp.
a=1
1(2×1 +1)= 1(2+1)= 1×3= 3
a=-2
-2(2×(-2) +1)= -2(-4 +1)=-2 -5= -7
a=4
4(2×4+1)= 4(8+1)= 4×9=36
a=-1
-1(2×(-1)+1)= -1(-2+1)= -1- 1= -2